KAJIAN PENERAPAN HEALTH, SAFETY, SECURITY AND ENVIRONMENT (HSSE) MANAGEMENT SYSTEM BERBASIS ISO PADA PT. PELINDO IV (PERSERO) TERMINAL PETIKEMAL BITUNG: Study of the Implementation of the ISO-Based Health, Safety, Security, and Environment (HSSE) Management System at PT. PELINDO IV (Persero) Bitung Container Terminal - Marthinus, Adrian Philip; Tjakra, Jermias; Malingkas, Grace Yoyce (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2024)
The implementation of the ISO-based Health, Safety, Security, and Environment (HSSE) Management System has become a critical demand in the industrial world to ensure safety, occupational health, security, and environmental protection in the workplace. At PT. Pelindo IV (Persero) Terminal Petikemas Bitung, as one of the main ports in Eastern Indonesia, the ISO-based HSSE Management System is crucial in addressing high work risks, especially with the intensive use of heavy equipment, a large workforce, and high material volume. This research aims to assess the implementation of the ISO-based Health, Safety, Security, and Environment (HSSE) Management System at PT. Pelindo IV (Persero) Terminal Petikemas Bitung. The study was conducted using a survey method through questionnaires and interviews, with the results processed into frequency distribution tables. The research concluded that the assessment of the ISO-based HSSE Management System implementation at PT. Pelindo IV (Persero) Terminal Petikemas Bitung was categorized as “good” in Leadership and Worker Participation, “good” in Planning, “good” in Support and Operation, “good” in Performance Evaluation, and “good” in Continual Improvement.